2016
DOI: 10.3390/pharmaceutics8030028
|View full text |Cite
|
Sign up to set email alerts
|

An Accelerated Release Study to Evaluate Long-Acting Contraceptive Levonorgestrel-Containing in Situ Forming Depot Systems

Abstract: Biodegradable polymer-based injectable in situ forming depot (ISD) systems that solidify in the body to form a solid or semisolid reservoir are becoming increasingly attractive as an injectable dosage form for sustained (months to years) parenteral drug delivery. Evaluation of long-term drug release from the ISD systems during the formulation development is laborious and costly. An accelerated release method that can effectively correlate the months to years of long-term release in a short time such as days or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Then these collected samples were deprotinised by using acetonitrile and then analyzed by using different analytical techniques like UV-spectroscopy, mass spectroscopy or ultra-performance liquid chromatography mass spectroscopy to obtain the data about plasma drug concentration of drug at different time interval. From obtained plasma drug concentration different pharmacokinetic parameters such as maximum plasma concentration, maximum time to reach maximum plasma concentration (t max ) and mean residence time can be determined [45][46][47][48][49][50][51][52][53][54] . CONCLUSION: From overall discussion it is concluded that the in-situ forming implants (ISFI) are the alternative drug delivery system to the frequently administered parental injections.…”
Section: Determination Of Drug Contentmentioning
confidence: 99%
“…Then these collected samples were deprotinised by using acetonitrile and then analyzed by using different analytical techniques like UV-spectroscopy, mass spectroscopy or ultra-performance liquid chromatography mass spectroscopy to obtain the data about plasma drug concentration of drug at different time interval. From obtained plasma drug concentration different pharmacokinetic parameters such as maximum plasma concentration, maximum time to reach maximum plasma concentration (t max ) and mean residence time can be determined [45][46][47][48][49][50][51][52][53][54] . CONCLUSION: From overall discussion it is concluded that the in-situ forming implants (ISFI) are the alternative drug delivery system to the frequently administered parental injections.…”
Section: Determination Of Drug Contentmentioning
confidence: 99%
“…The PLGA-PEG-PLGA thermo-gel markedly extended the release of LNG, which was promising for long-term contraception and fertility control [38]. The poly(lactide-co-glycolide) and polylactic acid polymer and a solvent mixture containing N-methyl-2-pyrrolidone and benzyl benzoate or triethyl citrate was be used as LNG-containing injectable in situ forming depot (ISD) system, then a long-time release of LNG was accomplished [39]. The star-shaped poly(D,L-lactic-co-glycolic acid)-b-methoxy poly(ethylene glycol) (4sPLGA-mPEG) block copolymer showed tuning sol-gel transition, controllable biodegradability, and excellent biocompatibility in vitro and in vivo, and also showed potential in many biomedical applications in our previous reports [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…They have been shown significant efficiency in cancer and also in other forms of diseases [20][21][22][23][24][25]. Formulation type can alter their biological activity in favor of cancer treatment [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%